Carbon‐11 Radiolabelling of Organosulfur Compounds: 11C Synthesis of the Progesterone Receptor Agonist Tanaproget. Issue 25 (12th May 2015) - Haywood, Tom; Kealey, Steven; Sánchez‐Cabezas, Santiago; Hall, James J.; Allott, Louis; Smith, Graham; Plisson, Christophe; Miller, Philip W.
Abstract Herein a new 11C radiolabelling strategy for the fast and efficient synthesis of thioureas and related derivatives using the novel synthon, 11CS2, is reported. This approach has enabled the facile labelling of a potent progesterone receptor (PR) agonist, [11C]Tanaproget, by the intramolecular reaction of the acyclic aminohydroxyl precursor with 11CS2, which has potential applications as a positron emission tomography radioligand for cancer imaging.